Women's Contribution Towards Islamic Da'wah at Kuala Lumpur - Mimi Hasliza Bt Ariffin (Universiti Sains Islam Malaysia, 2011)
This Academic Project discussed about the women's Towards Da'wah in Kuala Lumpur. The purpose of this research is to know about women's contribution in the Islamic da'wah. Among the activities are, religious talks, seminars, television forum, Islamic counseling and running the fardhu Ain classes for the family, local economic, society and religion. Islamic parenting courses are also given priority in the da'wah activities. This proves that Islamic women movements are not sidelined in the overall Islamic da'wah movements. To collect and gather the relevant data and information, the researcher uses the methodologies of literature review, interviews, field study and website search of the women da'wah group in Kuala Lumpur. The outcomes research of the research show that women are involved in the Islamic Da'wah movement and the role of women to fulfill the deeded in together effort to increase the Kalimah Allah.